PENGARUH E-SERVICE QUALITY DAN E-SERVICESCAPE TERHADAP E-LOYALTY PENGGUNA GOJEK MELALUI E-TRUST SEBAGAI VARIABEL INTERVENING DI KALANGAN MAHASISWA UNIVERSITAS WIDYA DHARMA KLATEN - Winanda, Dian Septyani; Nugroho, Arif Julianto Sri; Santoso, Imam (Widya Dharma Journal of Business - WIJoB, 2023)
This study aims to examine the effect of E-Service Quality and E-Servicescape on E-Loyalty of Gojek users through E-Trust as an intervening variable among students at Widya Dharma University, Klaten. The sample of this research is Widya Dharma Klaten University students with 140 respondents. The data collection method was carried out through distributing questionnaires to the respondents. The data obtained was then processed using SPSS version 22. Based on the results of this study it can be concluded: the direct effect of E-Service Quality on E-Trust, the direct effect of E-Servicescape on E-Trust, the direct effect of E-Service Quality on the E-Loyalty of Gojek users, the direct effect of E-Servicescape on the E-Loyalty of Gojek users, the direct effect of E-Trust on the E-Loyalty of Gojek users, the effect of E-Service Quality on E-Loyalty of Gojek users is intervened by E-Trust, and the effect of E-Servicescape on E-Loyalty of Gojek users is intervened by E-Trust.